1995
DOI: 10.1007/bf00017101
|View full text |Cite
|
Sign up to set email alerts
|

Global atmospheric change effects on terrestrial carbon sequestration: Exploration with a global C- and N-cycle model (CQUESTN)

Abstract: A b s t r a c tA model of the interacting global carbon and nitrogen cycles (CQUESTN) is developed to explore the possible history of C-sequestration into the terrestrial biosphere in response to the global increases (past and possible future) in atmospheric CO2 concentration, temperature and N-deposition. The model is based on published estimates of pre-industrial C and N pools and fluxes into vegetation, litter and soil compartments. It was found necessary to assign low estimates of N pools and fluxes to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 51 publications
(78 reference statements)
3
50
0
Order By: Relevance
“…In N-limited ecosystems such as the grassland investigated here, ecosystem C storage eventually becomes N-limited because C accumulation in soils requires concomitant sequestration of N (Gifford, Lutze & Barrett 1996;Rastetter et al 1992). This is also true for most natural and semi-natural ecosystems (Vitousek & Howarth 1991) in which longer-term organic C accumulation in soils is constrained to 1-12 g C m -2 a -1 (compiled data from a survey covering different biomes by Schlesinger 1996).…”
Section:    mentioning
confidence: 81%
“…In N-limited ecosystems such as the grassland investigated here, ecosystem C storage eventually becomes N-limited because C accumulation in soils requires concomitant sequestration of N (Gifford, Lutze & Barrett 1996;Rastetter et al 1992). This is also true for most natural and semi-natural ecosystems (Vitousek & Howarth 1991) in which longer-term organic C accumulation in soils is constrained to 1-12 g C m -2 a -1 (compiled data from a survey covering different biomes by Schlesinger 1996).…”
Section:    mentioning
confidence: 81%
“…Gifford [1994] and Gifford et al [1996] reported experimental results for r integrated over a 24 hour period of between 0.35 and 0.55 for wheat, pea, cotton, sorghum, bean, Eucalyptus and Pinus despite 2 orders of magnitude difference in plant mass and with growth temperatures ranging from 15°to 30°C. For wheat in another study, r fell between 0.39 and 0.44 [Gifford, 1995].…”
Section: A32 Respiration To Photosynthesis Ratiomentioning
confidence: 99%
“…The N that enters the soil is competed for by roots and microbes, the outcome of this competition depending on how the N is added and the initial conditions of the plants and microbial populations (Aber et al, 1989 ;Johnson, 1992). Gifford et al (1996) concluded that the assumption about how the exogenous N is initially taken up is a critical one that should be further investigated. Hudson, Gherini & Goldstein (1994) employed a very different approach to the calculation of Nstimulated C storage.…”
Section: Modelling Approachesmentioning
confidence: 99%
“…Their conclusion, based on results of CO # -manipulation and N-fertilization experiments, was that the ecosystem-level response of C assimilation to elevated CO # might depend on how N uptake by, and N recycling within, the vegetation influence the ability of plants to incorporate elevated CO # in the construction of canopy, stem, and root biomass. In TEM, N is allocated to represent the trade-off between canopy development and acclimation of tissue-level photosynthesis so that C uptake is maximized in building vegetative biomass at a specific C : N ratio which is not constant, however, because of seasonal changes in resorption and mobilization of N. Gifford et al (1996), using CQUESTN, emphasized that, because of compensations between C and N cycles, different model assumptions can lead to similar net results. For example, if a CO # stimulation of N mineralization was included (cf.…”
Section: Predictions From Ecosystem Modelsmentioning
confidence: 99%